Antihyperglycemic Activity of Alchemilla viridiflora Herb Methanol Extract in Streptozotocin-Induced Diabetic Male Rats - Jelena S. Radović Selgrad; Dušan J. Ušjak; Marina T. Milenković; Neda Lj. Milinković; Radmila M. Janković; Jovan B. Jevtić; Ksenija S. Mileski; Marjan S. Niketić; Tatjana D. Kundaković-Vasović (Molecules, 2025)
Based on the traditional use of Alchemilla L. species for the treatment of diabetes, the effect of the methanol extract of Alchemilla viridiflora (AVM) on enzyme activity in vitro and its impact on blood glucose levels in vivo were investigated. Diabetes was induced in male Sprague-Dawley rats using streptozotocin. AVM was administered to both normal and STZ-diabetic rats for 20 days at three different doses. Blood glucose levels and body weights of the treated animals were monitored throughout the experiment. After 20 days, serum insulin, cholesterol, triglycerides, and high- and low-density lipoproteins were measured. In addition, a histological analysis of the pancreas was performed. The AVM demonstrated inhibitory effects on the activities of all tested enzymes. In the in vivo experiment, a statistically significant reduction in body weight was observed in the AVM-treated animals at all three doses compared with the normal control group. Notably, a dose of 200 mg/kg significantly decreased blood glucose levels on both the 10th day and 20th day (p < 0.05). However, the extract showed no statistically significant effects on the tested biochemical parameters. Overall, the results of this study suggest that AVM has potential for the treatment of hyperglycemia associated with diabetes and obesity.